NARROWBAND INTERNET OF THINGS SECURITY THREATS AND COUNTERMEASURES (Modern education and development, 2025)
Internet of Things technologies have become an integral part of business and public life. This technology can be seen in almost every major city in Russia. Many leading countries are at a relatively high level of mass implementation of Internet of Things technology. Many areas of activity of the country directly depend on the Internet of Things: "smart home", "smart city", digital agriculture, automation of production, etc. At the same time, it is necessary to take into account that the diversified use of technologies entails a special interest of attackers and an increase in security threats. In this regard, experts have a question of ensuring security. This article discusses the characteristics of Internet of Things devices, the main security threats of narrowband Internet of Things and recommendations for countermeasures.